Integration of nematology as a training and research discipline in sub-Saharan Africa: progress and prospects - Cortada, L.; Dehennin, I.; Bert, W.; Coyne, D. (Brill, 2019)
Within sub-Saharan Africa (SSA), although nematodes are viewed among the most important threats to crop production and food security, the presence of trained nematologists working within this discipline has traditionally been viewed as scarce. The few research studies concerning this subject address this topic from a country or sub-regional perspective and generally portray nematology as ‘insufficient’. Over the past two decades, a few initiatives have been instrumental in building greater nematology expertise. For the first time a structured survey was undertaken, involving interviews with individuals from SSA that were (or currently are) involved in nematology training programmes, research, national extension services or in African universities. This paper provides evidence of the positive impact of various initiatives and shows an increase in the number of available nematology positions, together with high rates of graduates that return home to occupy qualified positions. Our findings will help researchers, policy makers and donors to identify areas requiring support to increase the promotion of nematology in SSA and to make an impact for end-users.